Stock market linkage and impact of the sub-prime mortgage crisis: evidence from Mainland China and Hong Kong - Wang, Zhao; Mohamed, Azali; Karbhari, Yusuf; Lau, Wei Theng (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This study investigates the linkage between Mainland China and Hong Kong stock markets pre and post 2007 U.S. sub-prime mortgage crisis. We employ Dynamic Conditional Correlation GARCH (generalised autoregressive conditional heteroscedasticity) model to identify the association of weekly market returns based on volatility spillover effects from 2000 to 2007 (pre-crisis), and 2008 to 2017 (post-crisis) respectively. Our study reports significant linkage between the two stock markets with the sub-prime mortgage crisis contributes to strengthening the relationship. In particular, based on the volatility spillover effect, the long-term equilibrium linkage between the two markets is steady and inseparable due to strong economic ties. Our results highlight the importance of policy implications, especially on how regulators should deal with the increased market interconnectedness and on the diversification opportunities by investors.